Couplage de modeles et de methodes numeriques pour I' electromagnetisme en domaine temporel - Remaki, Malika; Poupaud, Frederic; Fezoui, Loula; Chanrion, Olivier (European Journal of Computational Mechanics, 1999)
This paper deals with coupling models and/or methods in electromagnetism. The first part of the paper is devoted to the coupling of physical models (Vlasov-Poisson, VlasovMaxwell) which describe some field-particle interactions. In the second part, we present a new hybrid finite difference/ finite volume scheme applied to the time domain Maxwell equations.